'Collaborate to graduate': what works and why?. Issue 7 (10th November 2019) - Wilson, Kate F.; Wilson, Kate
ABSTRACT: Collaboration is recognised as valuable in enhancing students' learning as well as their social integration and sense of belonging at an institution, which lead to higher retention rates. We investigate the informal, self-organised collaborative practices of military and civilian engineering students in out-of-class settings using a mixed-methods approach including a weekly survey and in-depth interviews. We find that these students collaborate frequently and pervasively and have developed informal codes of ethics around sharing. Most of the students believe that collaboration with peers is the most effective form of study support. However, we also find that some students may remain isolated. The aspects of the institution and the engineering programme that support these collaborative processes are identified. These aspects include the concurrent military training, which fosters a collaborative rather than competitive or individualistic culture, residential accommodation, and the type of assessment used in engineering. Implications for non-military campuses are discussed.